2020
DOI: 10.1109/access.2020.3017135
|View full text |Cite
|
Sign up to set email alerts
|

Video Big Data Analytics in the Cloud: A Reference Architecture, Survey, Opportunities, and Open Research Issues

Abstract: The proliferation of multimedia devices over the Internet of Things (IoT) generates an unprecedented amount of data. Consequently, the world has stepped into the era of big data. Recently, on the rise of distributed computing technologies, video big data analytics in the cloud has attracted the attention of researchers and practitioners. The current technology and market trends demand an efficient framework for video big data analytics. However, the current work is too limited to provide a complete survey of r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 307 publications
0
7
0
Order By: Relevance
“…These devices are generating a huge amount of data as previously described. It is reported that the data produced by IoT devices will witness a growth of 28% by 2025 [223], where 65% of it is related to the surveillance cameras [224]. Even-though the conventional wisdom resorts to the centralized cloud servers for analytics owing to their high computational capacity, offloading these bulk of data presents scalability issues, as the access to the cloud can experience bandwidth bottleneck when the number of video sources increases.…”
Section: Intelligent Edge For Video Streamingmentioning
confidence: 99%
“…These devices are generating a huge amount of data as previously described. It is reported that the data produced by IoT devices will witness a growth of 28% by 2025 [223], where 65% of it is related to the surveillance cameras [224]. Even-though the conventional wisdom resorts to the centralized cloud servers for analytics owing to their high computational capacity, offloading these bulk of data presents scalability issues, as the access to the cloud can experience bandwidth bottleneck when the number of video sources increases.…”
Section: Intelligent Edge For Video Streamingmentioning
confidence: 99%
“…There are several works on video analysis in the context of big data. Aftab Alam et al provided a review on video big data analytics in the cloud and proposed a service-oriented architecture bridging the gap among large-scale video analytics challenges, big data solutions, and cloud computing [28]. Anjali et al (2019) conducted a survey on multiple object tracking for fast and parallel video processing in MapReduce with the Amazon EC2 Cloud [29].…”
Section: State Of the Art Overviewmentioning
confidence: 99%
“…e SaaS is a cloud technology paradigm implemented on cloud service providers' equipment and delivered to consumers via web applications and online interfaces. Users are not required to manage or develop [13]. PaaS may give operating applications and grow users as a secondary development platform.…”
Section: Logical Structure Of Cloud Technology Nist Divides Cloud Tec...mentioning
confidence: 99%